Estudo e desenvolvimento de instrumentação para monitoração de parâmetros fisiológicos em pacientes submetidos a oxigenoterapia hiperbárica (HBO) - Faria, Rubens Alexandre de (2011)
Hyperbaric chambers are a kind of equipament used to treat several illness or syndromes. However, it is very dangerous whenever electronic instruments are used inside it, because the chamber has oxygen (O2) under pressure and the equipment can originate fires, specially due to the generation of sparks. In the present work, it is described the development of an active biotelemetric device. The circuit is capable to monitor, in real time, the ECG signal of a patient during hyperbaric treatment. To minimize the possibility of generating temperature values high enough to initiate an explosion, it was chosen to use electronic circuits that, comparative, could operate with low levels of energy. Moreover, materials that when in contact with pure O2 could cause chemical reactions that would lead to an explosion, have been avoided. In this direction, it was chosen to feed the device using photovoltaic cells, thus avoiding the use of batteries. To reach this development, the necessary levels of electric field for the deflagration of electric sparks have been studied (by Paschen’s Curves) and tests inside a prototype hyperbaric chamber, using O2 under pressure, have been carried out. The final results define a safe relation between applied voltage and the conductive electronic circuit parts inside the chamber (copper trace and pads of the printed circuit board).